Acid fish silage in the diet of pacu and tambacu reared at cold suboptimal temperature - Corrêa, Camila Fernandes; Oliveira, Thaís da Silva; Leonardo, Antônio Fernando; Reis Neto, Rafael Vilhena; Enke, Dariane Beatriz Shoffen (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the supplementation of diet of pacu and tambacu with acid fish silage during winter. The experimental design was a 2 × 2 factorial arrangement (two genetic groups and two diets), with three replicates. The genetic group factor was composed of pacu (Piaractus mesopotamicus) and tambacu (♀Colossoma macropomum × ♂ Piaractus mesopotamicus). The two diets were based on plant ingredients; one of them was supplemented with acid fish silage (silage diet), and the other was a base diet without supplementation. Twelve net tanks, six from which with pacu, and six with tambacu, were used as experimental units, with ten fish in each tank. There was an interaction of the factors for final length, final weight, and daily weight gain. Pacu fed the silage diet showed a higher growth than pacu fed with the base diet; however, this effect was not observed for tambacu. A higher feed efficiency was observed for pacu than for tambacu, without a diet effect. The diet supplementation with acid fish silage improves the productive performance of pacu reared at cold suboptimal temperature, but it does not have this effect on tambacu.